MicroRNA-142 critically regulates group 2 innate lymphoid cell homeostasis and function - Roberts,LB; Jowett,GM; Read,E; Zabinski,T; Berkachy,R; Selkirk,ME; Jackson,I; Niazi,U; Anandagoda,N; Araki,M; Araki,K; Kasturiarachchi,J; et al. (Journal of Immunology, 2021)
Innate lymphoid cells are central to the regulation of immunity at mucosal barrier sites, with group 2 innate lymphoid cells (ILC2s) being particularly important in type 2 immunity. In this study, we demonstrate that microRNA(miR)-142 plays a critical, cell-intrinsic role in the homeostasis and function of ILC2s. Mice deficient for miR-142 expression demonstrate an ILC2 progenitor–biased development in the bone marrow, and along with peripheral ILC2s at mucosal sites, these cells display a greatly altered phenotype based on surface marker expression. ILC2 proliferative and effector functions are severely dysfunctional following Nippostrongylus brasiliensis infection, revealing a critical role for miR-142 isoforms in ILC2-mediated immune responses. Mechanistically, Socs1 and Gfi1 expression are regulated by miR-142 isoforms in ILC2s, impacting ILC2 phenotypes as well as the proliferative and effector capacity of these cells. The identification of these novel pathways opens potential new avenues to modulate ILC2-dependent immune functions.